Technostress: Pengertian, Penyebab dan Koping Pustakawan - Suryanto Suryanto; Twista Rama Sasi (Pustabiblia: Journal of Library and Information Science, 2017)
Nowadays, technology is growing so fast which cause all of the human life. Library is a kind of work which can’t lost from the impact of technological progress. Nevertheless, not all librarians are able to adapt quickly with the change and development of technology, so it can cause the problem for them, one of them is technostress. Technostress is an uncomfortable condition which which caused by the inability of individuals to adapt with the technological changes or a condition of individual dependency on technology which cause the uncomfortable both physical and psychic. Technostress is caused by several factors that is the development of technology, the lack of standardization, the lack of individual training (librarians) against the technology and equipment used, the technology reliability, the increased of work load which given to each librarian, the appearance of role change from the librarian. Another opinion says that which resulted in the occurrence of technostress there are five components, namely techno-overload, techno-invasion, techno-complexity, techno-insecurity, dan techno-uncertainty. Coping strategies which can be applied by librarians in facing technostress can be long-term coping methods, which is considered to be more effective to reduce the impact of technostress and short-term coping methods which is effective to overcome technostress temporarily.